Gene expression changes of single skeletal muscle fibers in response to modulation of the mitochondrial calcium uniporter (MCU) - Chemello, Francesco (Genom Data, 2015)
The mitochondrial calcium uniporter (MCU) gene codifies for the inner mitochondrial membrane (IMM) channel responsible for mitochondrial Ca(2 +) uptake. Cytosolic Ca(2 +) transients are involved in sarcomere contraction through cycles of release and storage in the sarcoplasmic reticulum. In addition cytosolic Ca(2 +) regulates various signaling cascades that eventually lead to gene expression reprogramming. Mitochondria are strategically placed in close contact with the ER/SR, thus cytosolic Ca(2 +) transients elicit large increases in the [Ca(2 +)] of the mitochondrial matrix ([Ca(2 +)]mt). Mitochondrial Ca(2 +) uptake regulates energy production and cell survival. In addition, we recently showed that MCU-dependent mitochondrial Ca(2 +) uptake controls skeletal muscle trophism. In the same report, we dissected the effects of MCU-dependent mitochondrial Ca(2 +) uptake on gene expression through microarray gene expression analysis upon modulation of MCU expression by in vivo AAV infection. Analyses were performed on single skeletal muscle fibers at two time points (7 and 14 days post-AAV injection). Raw and normalized data are available on the GEO database (http://www.ncbi.nlm.nih.gov/geo/) (GSE60931).